Peningkatan Kualitas Keagamaan Jamaah Ibu-Ibu Desa Bekiring Melalui Pelatihan Bilal Tahlil - Rima Alfiatul Azizah; Hanafi Hadi Susanto (Social Science Academic, 2023)
This study aims to determine the increase in the religious quality of the congregation of Bekiring Village women through community service in the form of Bilal Tahlil training. The method used in this research is ABCD (Asset Based Community Driven-Development) in the form of providing education in the form of Bilal Tahlil training by providing guidance and assistance in learning to read Tahlil properly and correctly. The result of this training is an increase in the religious quality of the congregation of Bekiring Village women which can be seen by the abilities possessed by the training participants in becoming Leader Bilal Tahlil after participating in the Bilal Tahlil training.